Bioactive compounds of interest to the food industry: properties, applications and perspectives for the consumer market (Research, Society and Development, 2020)
Functional foods are a market trend due to the possibility of manufacturing more beneficial processed products, with health benefits and sensorially pleasant, adding value to the products. This research aimed to review the properties of the bioactive compounds β-glucans, inulin, psyllium, chitosan, and lycopene, demonstrating the possibilities of their use by the food industry in the development of new products. Their composition, technological applications, and functional characteristics were presented. These bioactive compounds have high possibilities of use in bakery products, dairy products, meat products, and beverages. From the technological point of view, the Brazilian food industry can explore its applications in the reformulation of healthier products, with different textures and market appeals.